4-th Conference “Statistical Physics: Modern Trends and Applications” (Lviv, July 3–6, 2012) (Condensed Matter Physics, 2011)
Next year (July 3–6, 2012) the Institute for Condensed Matter Physics of the National Academy of Sciences of Ukraine (Lviv) plans to organize the 4-th Conference “Statistical Physics: Modern Trends and Applications”. This Conference continues a tradition of regular international meetings in statistical physics in Ukraine, established in the 1970-ies and renewed by “Statistical Physics-2005. Modern Problems and New Applications” (Lviv), “Statistical Physics-2006. Condensed Matter: Theory and Applications” (Kharkiv) and the 3-rd Conference “Statistical Physics: Modern Trends and Applications” (Lviv, 2009).